Henry Kissinger, World Order: Reflections on the Character of Nations and the Course of History - Ms. Hajira Asaf Khan (CISS Insight Journal, 2015)
“In every era, humanity produces demonic individuals and seductive ideas of repression. The task of statesmanship is to prevent their rise to power and sustain international order.”The aforementioned excerpt, perhaps sums up the political thinking of Henry Kissinger in the field of diplomacy. A staunch realist and a seasoned practitioner of international relations, Kissinger has, in his ninety-first year of life, written yet another book among numerous others, including ‘On China’ and ‘Diplomacy’ being his most-read works around the globe. He has served as Secretary of State to both Presidents Nixon and Gerald Ford and has on many occasions been sought by the US leadership for insight and advice on varying issues regarding US strategic and foreign policy. Needless to say, his profound knowledge and long experience of dealing with various world powers, along with his deep insight on interstate relations and conduct of great powers in history, put him in a unique position to write on the evolution of regional and global political systems—their strengths and weaknesses, their wisdom and peculiarities.